A unidirectional TM-wave cloak with full parameters - Wang, Huaping (2021)
Unidirectional cloaks or carpet cloaks have become an essential branch of invisibility cloaks due to non-extreme parameters that are relatively easy for realization and potential applications. So far, a unidirectional cloak for transverse electric (TE) polarized wave has been successfully realized to hide an object in the air along a single direction with almost ideal performance. However, a practical method to achieve a unidirectional cloak for transverse magnetic (TM) polarization is still missing. In this paper, we successfully have designed, fabricated, and measured a full-parameter unidirectional TM-wave cloak in free space. In comparison to the previously-realized TE-wave counterpart, our cloak uses a perfect electric conductor boundary to obey the free-space symmetry condition of the TM incident wave and is therefore much more convenient to fabricate. The cloaking performance of the fabricated sample has been demonstrated via both full-wave numerical simulation and near-field measurement.